2016
DOI: 10.1159/000368544
|View full text |Cite
|
Sign up to set email alerts
|

Hypertensive/Microvascular Disease and COPD: a Case Control Study

Abstract: Background/Aims: This study tested the hypothesis that individuals with chronic obstructive pulmonary disease (COPD) have more small vessel disease and more severe disease than an age- and gender- matched hospital patient comparison group. Methods: This was a single centre, case-control study of 151 individuals with COPD (FEV1/VC) < 0.7 recruited consecutively immediately after respiratory function tests at a Melbourne teaching hospital over a 4 month period in 2010. Controls were individuals with normal respi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

2
18
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 11 publications
(20 citation statements)
references
References 29 publications
2
18
0
Order By: Relevance
“…To date, systematic studies characterizing the retinal microvasculature in patients with COPD are scarce. Data from a population study suggest that the width of retinal venules is inversely associated with forced expiratory volume in one second (FEV 1 ) and FEV 1 /forced vital capacity (FVC) 26,27 . This would indicate that vascular comorbidities associated with obstructive decrements in lung function may be characterized by defects in the microvascular circulation, as assessed with fundus imaging 26 .…”
mentioning
confidence: 99%
“…To date, systematic studies characterizing the retinal microvasculature in patients with COPD are scarce. Data from a population study suggest that the width of retinal venules is inversely associated with forced expiratory volume in one second (FEV 1 ) and FEV 1 /forced vital capacity (FVC) 26,27 . This would indicate that vascular comorbidities associated with obstructive decrements in lung function may be characterized by defects in the microvascular circulation, as assessed with fundus imaging 26 .…”
mentioning
confidence: 99%
“…Multivariate analyses also demonstrated that COPD remained an independent determinant of microvascular retinopathy after adjusting for hypertension, smoking, gender and diabetes (Chew et al. ).…”
Section: Methodsmentioning
confidence: 96%
“…In addition, microvascular retinopathy was classified as mild (arteriovenous nicking, focal arteriolar narrowing, silver‐wiring or a decreased AVR), moderate (haemorrhage or exudates) or severe (papilledema) (Chew et al. ). Chew et al.…”
Section: Methodsmentioning
confidence: 99%
See 2 more Smart Citations